Between resistance and status quo: Cultural dynamics of online climate denial - Bresolin, Elettra (2023)
Although it has become vital for the social sciences to study the phenomenon of climate skepticism (or denial), the majority of studies reviewed have overlooked its cultural dimensions. The aim of this article is to identify the climate change imaginaries that are constructed and circulated in the Watts Up With That? Facebook group, and the narratives that are used to sustain them discursively. By means of an analysis of group posts and discussions, I show that these nurture a skeptical discourse in which a few recurrent themes create a polarized moral landscape, and are discussed in an environment of self-legitimization and rejection of the official scientific discourse. As my main conclusion, I propose that climate change denial represents a defense of the status quo, and constructs an environmental imaginary which is based on the separation between human beings and nature, and on the Enlightenment narrative of infinite progress.